PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI MODEL COOPERATIVE INTEGRATED READING COMPOSITION (CIRC) PADA SISWA SDN 8 METRO BARAT - Fentika, Ade Gilda; Adiwijaya, Satria Nugraha (Prodi PGMI STIT Sunan Giri Bima, 2025)
This research aims to improve students reading comprehension skills through the Cooperative Integrated Reading And Composition (CIRC) model in fourth grade students at SD Negeri 8 Metro Barat. This study uses the Classroom Action Research (CAR) type which is carried out in two cycles, with each cycle consisting of three meetings. Each cycle has four stages of activity, namely, planning, implementation, observation, and reflection. The subjects of this study were 25 fourth grade students of SD Negeri 8 Metro Barat, consisting of 10 male students and 15 female students. Data collection methods used include test sheets, observations and interviews. Data analysis techniques include quantitative and qualitative analysis. The results of the study showed that student learning outcomes in reading comprehension skills in the Indonesian language subject in cycle I were 40% and in cycle II there was an increase of 44% to 84%. From the results of observations in the learning process, there are factors that support the improvement of reading comprehension skills through the application of the CIRC model, namely student involvement in group work, student courage in expressing opinions, active in asking questions, and focus in learning. By using the CIRC model, students can be trained and encouraged to understand a reading text correctly and appropriately, so that it can improve students reading comprehension skills. Abstrak Penelitian ini bertujuan untuk meningkatkan kemampuan membaca pemahaman siswa melalui model Cooperative Integrated Reading And Composition (CIRC) pada siswa kelas IV di SD Negeri 8 Metro Barat. Penelitian ini menggunakan jenis Penelitian Tindakan Kelas (PTK) yang dilakukan dalam dua siklus, dengan setiap siklus terdiri dari tiga pertemuan. Setiap siklus memiliki empat tahapan kegitan yaitu, perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah 25 siswa kelas IV SD Negeri 8 Metro Barat, terdiri dari 10 siswa laki-laki dan 15 siswa perempuan. Metode pengumpulan data yang digunakan mencakup lembar tes, observasi dan wawancara. Adapun teknik analisis data meliputi analisis kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa hasil belajar siswa pada kemampuan membaca pemahaman mata pelajaran Bahasa Indonesia pada siklus I adalah 40% dan pada siklus II terjadi peningkatan sebesar 44% menjadi 84%. Dari hasil pengamatan pada proses pembelajaran terdapat faktor-faktor yang mendukung peningkatan kemampuan membaca pemahaman melalui penerapan model CIRC adalah keterlibatan siswa dalam kerja kelompok, keberanian siswa dalam mengemukakan pendapat, aktif dalam bertanya dan fokus dalam pembelajaran. Dengan menggunakan model CIRC ini dapat melatih dan mendorong siswa dalam memahami suatu teks bacaan dengan tepat dan sesuai, sehingga dapat meningkatkan kemapuan membaca pemahaman siswa.